Portrayals of translation and interpreting in an early trinidadian novel: a case study of “Warner Arundell: The adventures of a creole” - Hoyte-West, Antony (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2024)
Commonly held to be the first Trinidadian novel, E. L. Joseph’s Warner Arundell: The Adventures of a Creole was first published in 1838. Presented as a fictional memoir, the book’s wide-ranging plot spans many of the geographical, cultural, and linguistic spaces which characterised the Caribbean during the early nineteenth century. Though language and multilingualism play an important role in the novel and have been discussed in scholarly analyses, this study zooms in on the representation of translation and interpreting in the novel. With the book’s hero a gifted linguist, his skills as a translator and interpreter are often highly relevant to key moments in the work’s intricate chain of events. As such, in the first instance, a brief overview of selected historical and fictional aspects of translation and interpreting in the Caribbean context is given, as well as some remarks on the history of the Caribbean and on the biography of the book’s author. The novel’s three volumes are then analysed, and relevant scenes involving translation and/or interpreting are highlighted and discussed. Lastly, the conclusion offers some general thoughts on the role of literary analyses with regard to the history of translation and interpreting in colonial milieux.